Liquid foam templates associated with the sol-gel process for production of zirconia ceramic foams - Beozzo, Cristiane Carolina [UNESP]; Alves-Rosa, Marinalva Aparecida [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP] (MDPI, 2013)
The unique properties of ceramic foams enable their use in a variety of applications. This work investigated the effects of different parameters on the production of zirconia ceramic foam using the sol-gel process associated with liquid foam templates. Evaluation was made of the influence of the thermal treatment temperature on the porous and crystalline characteristics of foams manufactured using different amounts of sodium dodecylsulfate (SDS) surfactant. A maximum pore volume, with high porosity (94%) and a bimodal pore size distribution, was observed for the ceramic foam produced with 10% SDS. Macropores, with an average size of around 30 μm, were obtained irrespective of the SDS amount, while the average size of the supermesopores increased systematically as the SDS amount was increased up to 10%, after which it decreased. X-ray diffraction analyses showed that the sample treated at 500 °C was amorphous, while crystallization into a tetragonal metastable phase occurred at 600 °C due to the presence of sulfate groups in the zirconia structure. At 800 and 1000 °C the monoclinic phase was observed, which is thermodynamically stable at these temperatures. © 2013 by the authors; licensee MDPI, Basel, Switzerland.
Keywords: Ceramic foam; Liquid-foam templates; Sol-gel; Surfactant; Thermal treatment; Bimodal pore size distribution; Crystalline characteristic; Metastable phase; Monoclinic phase; Thermal treatment temperature; Thermodynamically stable; Zirconia ceramic; Heat treatment; Liquids; Sodium dodecyl sulfate; Sol-gel process; Surface active agents; X ray diffraction; X ray diffraction analysis; Zirconia; Ceramic foams